RANCANG BANGUN SISTEM E-COMMERCE BERBASIS CODEIGNETER FRAMEWORK PADA UMKM THRIFT M.S - situmeang, murni; Amrizal (Computer Science and Industrial Engineering, 2023)
E-Commerce or Electronic Commerce is one of the individual or group businesses that sell /buy goods online, one of which is Umkm Thrift M.S which is engaged in the sale of imported and non-imported used clothes with korean style models, with the process of selling and marketing goods still conventionally so that it is less known by buyers and unsatisfactory income for Thift M.S. Seeing this need, it is necessary to have an online sales system including reports related to the thrift m.s information system, by building a website in the field of sales to promote products through the website, and can be used as a means to transact buying and selling goods or products and conduct sales transactions with a relatively short time and distance, because the internet can cover a wide market to introduce and market products, this will be very useful for Umkm Thrift M.S